Tanggung Jawab Pelaku Usaha Terhadap Cacat Tersembunyi Pada Sepeda Motor Baru - Vika Chairil Bachta; Teng Berlianty; Theresia Louize Pesulima (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Consumers generally do not know the parts of motorbikes, so it is possible that business actors already know that there are hidden notes on the motorbike and violate consumer rights. Business actors should provide guarantees to consumers as motorbike buyers by providing guarantees in accordance with their rights consumer.Purposes of the Research: This writing aims to examine the dealer's responsibility for hidden defects in the sale and purchase of new motorcycles and to examine the legal remedies that can be taken by consumers for hidden defects in the sale and purchase of new motorcycles.Methods of the Research: The type of research used is normative, which is focused on providing explanations that explain a particular category. Approach the problem of the statute approach (statute approach) and the conceptual approach (conceptual approach). The collection of legal materials through primary legal materials is then free from secondary legal materials. The processing and analysis of legal materials is described in a qualitative way with the aim of describing the findings in the field.Results of the Research: The responsibility given by the seller is that if there is a hidden defect in the new motorcycle, the seller is obliged to exchange or replace the goods in accordance with the agreement contained in the warranty card. Legal remedies that can be taken by consumers are the enactment of the UUPK, especially Article 19 paragraph (1) and Article 24 concerning consumer protection, which aims to provide a legal basis for consumers to claim their rights. Product responsibility for motorcycles that contain hidden defects is one solution that can be applied to a motorcycle sale and purchase agreement if there are hidden defects because the implementation of product responsibility allows consumers to directly ask for a replacement from the seller who has been negligent in selling the motorcycle and cause harm to the buyer, namely the consumer